Distribution pattern of endophytic bacteria and fungi in tea plants - Lin, Haiyan; Liu, Changwei; Peng, Zhong; Tan, Bin; Wang, Kunbo; Liu, Zhonghua (Frontiers in Microbiology, 2022)
Endophytes are critical for plant growth and health. Tea is an economically important crop in China. However, little is known about the distribution pattern and potential functions of endophytic communities in tea trees. In this study, two genotypes (BXZ and MF) cultivated under the same conditions were selected, and endophytic bacteria and fungi were analyzed through 16S rRNA and ITS high-throughput sequencing technologies, respectively. For endophytic bacteria, root tissues harbored the most diverse endophytes, followed by stems and old leaves, and new leaves possessed the lowest diversity. In contrast, old leave tissues harbored more diverse endophytic fungi than did root and stem tissues. Most of the dominant endophytes showed obvious cultivar and tissue preferences. Tissue type played a more important role in shaping community structure than did cultivar. Nevertheless, some endophytic bacterial groups, which mainly affiliated to Chryseobacterium, Sphingomonas, Rhizobium, Morganella, Methylobacterium and Comamonadaceae, could parasitize different tissues, and the average relative abundance of endophytic bacteria was as high as 72.57%. Some endophytic fungal populations, such as Colletotrichum, Uwebraunia, Cladosporium, and Devriesia, could also parasitize tea, and the relative abundance accounted for approximately 25.70–97.26%. The cooperative relationship between endophytic bacteria and fungi in the new leaves was stronger than that in the old leaves, which can better participate in the metabolism of tea material.